NILAI-NILAI PROPHETIC LEADERSHIP PESERTA DIDIK PADA PEMBELAJARAN YANBUÃƒÆ’Ã‚Â (STUDI KASUS SISWA KELAS IV MI ISLAMIYAH DESA SEPANJANG KECAMATAN GLENMORE) - Ayu Safitri; Kurniyatul Faizah; Sudarsri Lestari (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2022)
ABSTRACK This study aims to determine the implementation of prophetic leadership values ​​in fourth grade students in yanbu'a MI ISLMIYAH learning in the village of Panjang District, Glenmore. This type of research is a qualitative case study. The subjects of this study were fourth grade students. Data collection techniques in this study were observation, interviews, and documentation. The research instrument used interview guidelines and observation sheets. Data analysis techniques in this study consisted of data collection, data reduction, data display, conclusion drawing. The values ​​of prophetic leadership are the personality of the Prophet which consists of four characteristics, namely: shiddiq (honest), amanah (trustworthy), tabligh (delivering clearly), fathanah (intelligent). The results show that the implementation of the values ​​of prophetic leadership, namely: shiddiq (honest), amanah (trustworthy), tabligh (delivering clearly), fathanah (intelligent) in yanbu'a learning has been embedded in students during yanbu' learning activities. a takes place. This is supported by guidance from the teacher, the media used when learning yanbu'a, high self-confidence, and good emotional intelligence of students. Keywords: Prophetic Leadership Values, Yanbu'a Learning